Automatic Generation of Unit Test Data for Dynamically Typed Languages - Hayatou Oumarou; El Mansour, Faouzi (AI Society & STMIK Indonesia, 2023)
Testing is the major means of verifying and validating software. It is a repetitive and time-consuming activity. Testing is neglected because of its high cost and the fact that it does not add functionality to the system. As a result, many programmers don't write tests. To remedy this, some researcher proposed automatic test generation. Test generation is a solution that reduces workload and increases productivity. In this paper, we propose a test data generation approach for unit tests in dynamically typed languages. Our approach is based on the analysis and decomposition of the AST (Abstract Syntax Tree) obtained when compiling the source code of the method under test. We validate this approach in Pharo a real system. The results on three systems show the effectiveness of the approach.